2001
DOI: 10.1046/j.1365-2591.2001.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of computed tomography when comparing nickel–titanium and stainless steel files during preparation of simulated curved canals

Abstract: Ni-Ti instruments produced preparations with adequate enlargement, less transportation, and a better centring ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
62
0
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 20 publications
1
62
0
8
Order By: Relevance
“…less straightening or decentralization of the canal, and a rounder canal preparation even in severely curved root canals. [3][4][5][6][7] Deviation from the original curvature can lead to excessive or inappropriate dentin removal, straightening of the canal and creation of ledge in the dentinal wall, a biomechanical defect known as elbow, which forms the coronal to the elliptical-shaped apical seal, canals with…”
Section: Introductionmentioning
confidence: 99%
“…less straightening or decentralization of the canal, and a rounder canal preparation even in severely curved root canals. [3][4][5][6][7] Deviation from the original curvature can lead to excessive or inappropriate dentin removal, straightening of the canal and creation of ledge in the dentinal wall, a biomechanical defect known as elbow, which forms the coronal to the elliptical-shaped apical seal, canals with…”
Section: Introductionmentioning
confidence: 99%
“…The simulated canals in resin blocks used in this study does not permit the action of the instruments in root canals of real teeth because of differences in the surface texture, hardness and cross-section. However, resin blocks allow a direct comparison of the shaping ability of different instruments and studies on extracted teeth fully confirmed observations made on resin blocks 3,5) . As use of simulated canals in resin blocks would have more binding of instruments, the study of with the use of real teeth will be necessary.…”
Section: ⅳ Discussionmentioning
confidence: 56%
“…NiTi instruments have two to three times higher elastic flexibility and a superior resistance to torsional fracture, compared with similar-sized conventional stainless steel instruments [1][2][3][4][5] . Also, rotary instrumen- The aims of this study were to compare the shaping effect and safety between single length technique recommended by manufacturer and crown-down technique using Mtwo rotary file and to present a modified method in use of Mtwo file.…”
Section: ⅰ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important parameter for evaluating the effectiveness of instruments is their ability to deliver efficient cleaning and shaping while preserving the Table 1 Statistical values of the instruments used Table 2 Statistical values on coronal leakage (P < 0.05) Table 3 Statistical values on apical leakage curvature of the canal during the operation (14). Various studies have reported that the utilization of nickel titanium instruments, by causing less transportation than stainless steel instruments at both the middle and apical thirds, results in shaping at the apical third that closely resembles the original canal form (15). The literature also indicates that motor-driven nickel titanium instruments create canal shapes that are more circular and homogeneous in form (1).…”
Section: Discussionmentioning
confidence: 99%